PENERAPAN RELAKSASI OTOT PROGRESIF PADA PEKERJA KONTRUKSI BANGUNAN DENGAN PENGUKURAN NORDIC BODY MAP - Abri Madoni; Noly Papertu Englardi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Construction workers are jobs engaged in the construction of facilities and infrastructure. Every worker must have risks to their work, one of the risks experienced by construction workers is musculoskeletal disorders. Indonesia in 2016-2018 recorded workers with MSDs as many as 26.74%. While the city of Padang in 2018-2021 recorded as many as 60,283 people experiencing MSDs. Measurement of these MSDs can be done with the Nordic Body Map questionnaire. One of the nursing actions to reduce musculoskeletal disorders for workers is Progressive Muscle Relaxation. The purpose of this study was to determine the effect of PMR with MSDs. The design used in this study is a quantitative research design with a quasi-experimental research design with pre and post tests without control. The results of the study showed that the average difference in the level of musculoskeletal disorders before and after doing progressive muscle relaxation therapy was 31,100 with a standard deviation of 4.748. From the results of the paired T-Test, the p-value (0.000) or p 0.05 was obtained. it can be concluded that there is a significant difference between the level of complaints of musculoskeletal disorders before and after being given PMR therapy.